Wireless Temperature Control Plant Model Using LabVIEW - Wandee Petchmaneelumka; Apinai Rerkratn; Vanchai Riewruja (My University, 2023)
This paper presents a wireless temperature control plant. The proposed system consists of RTD PT1000 temperature sensor, Wheatstone bridge circuit, amplifier circuit, ESP32 module, SCR power regulator, incandescent lamp, and LabVIEW program for controlling and monitoring temperature of plant. The RTD PT1000 sensor is used for measuring the temperature of plant and converting to voltage by Wheatstone bridge circuit before sent the output voltage to analog input port of ESP 32 module. The TCP/IP protocol is used to communicate between LabVIEW program and ESP32 module via WIFI network. LabVIEW program is employed to monitor and control temperature of plant via display screen. The experimental testing with various conditions shows that the proposed system can monitor and control temperature of plant with satisfactory values without the cables connecting between the temperature plant and the control unit.
Keywords: IoT-based Smart Home Systems; Industrial Automation and Control Systems; Energy Efficient Wireless Sensor Networks